2007
DOI: 10.1007/s12149-007-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Normal uptake of 18F-FDG in the testis: an assessment by PET/CT

Abstract: Some uptake of FDG is observed in the normal testis and declines slightly with age. Physiological FDG uptake in the testis should not be confused with pathological accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 21 publications
5
45
2
1
Order By: Relevance
“…In the present study, 18 F-FDG PET/CT was performed in 66 normal healthy men, and a significant negative correlation was found between T/M ratio and age, which is consistent with the results of a previous study [6]. However, no significant correlation was found between mean testicular SUV and age, which does not concur with the findings of Kazuhiro et al, in which a weak, albeit significant negative correlation was found between the two [5]. There may have been other factors affecting testicular SUV such as testicular volume or sexual activity.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In the present study, 18 F-FDG PET/CT was performed in 66 normal healthy men, and a significant negative correlation was found between T/M ratio and age, which is consistent with the results of a previous study [6]. However, no significant correlation was found between mean testicular SUV and age, which does not concur with the findings of Kazuhiro et al, in which a weak, albeit significant negative correlation was found between the two [5]. There may have been other factors affecting testicular SUV such as testicular volume or sexual activity.…”
Section: Discussionsupporting
confidence: 89%
“…However, ages in this study were more evenly distributed than in previous studies. Kazuhiro et al evaluated 203 cancer patients, however only 6 subjects were aged 30-39 years and no subjects were 20-29 years old [5]. Twenty-one percent of subjects were under 40 years old in our study, whereas only 2.95% of subjects were under 40 years old in Kazuhiro's study.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations